Problems at the human-horse interface and prospects for smart textile solutions - McGreevy, P. D.; Sundin, M.; Karlsteen, M.; Berglin, L.; Ternström, J.; Hawson, L.; Richardsson, H.; McLean, A. N. (Journal of Veterinary Behavior Clinical Applications and Research, 2014)
The significant potential for so-called "smart textiles" in the design of the next generation of devices that measure pressure, tension, moisture, and heat at the human-horse interface is discussed in this article. Research techniques from theoretical and experimental physics laboratories, combined with wireless technology, can be readily adapted to measure and store metrics for numerous variables in equine structure and function. Activities, such as breathing, the extension and flexion of joints, limb kinematics, and cardiac function, can be logged as indicators of physiological and behavioral conditioning (training). Such metrics may also, one day, support veterinary diagnostics but also play a role in safeguarding sport-horse welfare, especially in elite contexts where the horse may be pushed to its functional limits. As such, they are likely to emerge as an area of great interest to equitation and welfare scientists. It is important to note that smart textiles sense and react to exogenous stimuli via integrated sensors. So, beyond the equitation science laboratory, the emergence of polymers and smart materials may enhance the effectiveness of, or challenge us to completely rethink, traditional items of saddlery, thus improving equitation. The integration of smart textiles in all sorts of extant and emergent equipment for everyday equestrians could, in the future, lead to equipment that responds appropriately to the demands of equitation in its various forms. Rethinking equitation through physics and the use of smart textiles seems to have merit in that it is a novel means of both investigating and addressing problems that compromise the welfare and performance of horses. The purpose of this article is to envision the use of smart textiles in research, clinical, equestrian, and horse care contexts.